Truancy prevention and intervention a practical guide - Bye, Lynn. (New York ; Oxford : Oxford University Press, 2010)
This practical guide covers best practices in truancy at the community, school, and student/family levels of interventions providing an essential everyday reference guide to research-based programs and truancy program implementation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School attendance -- United States